2020
DOI: 10.3350/cmh.2020.0094
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the complement system in alcohol-induced liver disease

Abstract: Alcohol-induced liver disease (ALD) is a complex disorder, with a disease spectrum ranging from steatosis to steatohepatitis, cirrhosis, and hepatocellular carcinoma. Although the pathogenesis of ALD is incompletely understood and currently no effective drugs are available for ALD, several lines of evidence suggest that complement activation and oxidative stress play crucial roles in the pathogenesis of ALD. Complement activation can regulate the production of ROS and influence oxidative stress in ALD. Precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Neuroimmune pathways were commonly enriched for multiple SE events, including TNF, NF- κB, IL6-JAK-STAT3, IL2-STAT5, NOD-like receptor (NLR) signaling pathways, as well as T cell activation and differentiation (Supplementary Table S6 ). Noteworthy, the complement cascade, which is part of the innate immune system involved in alcoholic liver disease [ 62 ], was enriched for the SE events in ELOVL7, LINC00665 , NSUN4 , and SRRM2 . We also found that epithelial-mesenchymal transition (EMT) was enriched for the SE events in ELOVL7 , SRRM2 and TBC1D5 and was depleted for DRC1 and LINC00665 in GSEA.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimmune pathways were commonly enriched for multiple SE events, including TNF, NF- κB, IL6-JAK-STAT3, IL2-STAT5, NOD-like receptor (NLR) signaling pathways, as well as T cell activation and differentiation (Supplementary Table S6 ). Noteworthy, the complement cascade, which is part of the innate immune system involved in alcoholic liver disease [ 62 ], was enriched for the SE events in ELOVL7, LINC00665 , NSUN4 , and SRRM2 . We also found that epithelial-mesenchymal transition (EMT) was enriched for the SE events in ELOVL7 , SRRM2 and TBC1D5 and was depleted for DRC1 and LINC00665 in GSEA.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol can be metabolized to ROS by alcohol dehydrogenase (ADH) and Advances in Pharmacological and Pharmaceutical Sciences CYP2E1 [68]. ROS are released extensively, triggering toxic efects directly or indirectly through lipid peroxides [69]. A recent study reported that ethanol-induced liver injury and lipid peroxidation correlate with the CYP2E1 activity [70].…”
Section: Kaempferol Suppresses the Hepatic Activity Of Cyp2e1mentioning
confidence: 99%
“…For instance, C3, factor B, and factor D activate the alternative pathway, leading to the generation of anaphylatoxins C3a and C5a, which induce insulin resistance and disrupt lipid metabolism in the liver ( 352 ). C1q contributes to liver injury by activating the classical complement, whereas factor D protects against ethanol-induced inflammation and promotes hepatic healing and recovery ( 353 , 354 ). Several experimental models have demonstrated that complement inhibition is beneficial for liver injury (including IRI), liver transplantation, and acute liver failure.…”
Section: Liver and Diseasesmentioning
confidence: 99%